2017
DOI: 10.1128/aac.00448-16
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Nitrite Inhibits Killing of Pseudomonas aeruginosa Biofilms by Ciprofloxacin

Abstract: Sodium nitrite inhibits bacterial respiration and is in development as an antimicrobial for chronic bacterial infections associated with cystic fibrosis. The goal of the current study was to investigate the interaction between nitrite and ciprofloxacin. Using liquid culture killing assays and a biotic biofilm model, we observed that nitrite induces tolerance of ciprofloxacin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…In such conditions, antibiotic efficacy is linked to respiratory activity; for example, deletion of the cytochrome oxidases, which reduces respiration, inhibits drug lethality [34], while deletion of ATP synthase subunits, which increases respiration, enhances lethality [34,69]. Similarly, respiratory suppression by nitrite also inhibits antibiotic killing [70]. Under anoxia, nitrate frequently participates in anaerobic respiration as the terminal electron acceptor and can potentiate antibiotic killing [33]; it is not yet known if nitrate and other terminal electron acceptors also generate toxic metabolic byproducts that contribute to antibiotic death processes.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…In such conditions, antibiotic efficacy is linked to respiratory activity; for example, deletion of the cytochrome oxidases, which reduces respiration, inhibits drug lethality [34], while deletion of ATP synthase subunits, which increases respiration, enhances lethality [34,69]. Similarly, respiratory suppression by nitrite also inhibits antibiotic killing [70]. Under anoxia, nitrate frequently participates in anaerobic respiration as the terminal electron acceptor and can potentiate antibiotic killing [33]; it is not yet known if nitrate and other terminal electron acceptors also generate toxic metabolic byproducts that contribute to antibiotic death processes.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…The study has demonstrated that nitrite could be safely applied to reach millimolar concentrations in the airway surface liquid, paving the road for the agent to be a previously unidentified antimicrobial therapy. Nitrite has also been found to be either cooperative or antagonistic when used in combination with antibiotics in Pseudomonas aeruginosa 8,10,11 . These effects are a result of the bacteriostatic action, which does not require NO as an intermediate 1 .…”
mentioning
confidence: 99%
“…Tolerance induced by nitrite to aminoglycosides and Cip is proposed to be attributed to impaired respiration (oxygen consumption rate, hereafter referred to as respiration) given similar effects of other respiratory inhibitors, such as cyanide and carbonyl cyanide m-chlorophenylhydrazone (CCCP) 10,11 . As nitrite is bacteriostatic, this proposal is in perfect agreement with the recent report that antibiotic efficacy is linked to bacterial cellular respiration 13 .…”
mentioning
confidence: 99%
See 2 more Smart Citations